Protective Effects of L-Carnitine on Growth and Cardiac Function in High-Glucose-Exposed Zebrafish Embryos - Editya Fukata; Anditri Weningtyas; Lintang Widya Sishartami; Nuramaliah Desliani Putri; Putri Kusuma C. G. R. Asfandi (Biology, Medicine, & Natural Product Chemistry, 2025)
Diabetes mellitus is a chronic metabolic disorder, and maternal hyperglycaemia during pregnancy increases the risk of fetal developmental complications. This study aimed to evaluate the protective role of L-carnitine against glucose-induced embryotoxicity in zebrafish (Danio rerio). Fertilized embryos were exposed to 5% glucose with or without L-carnitine supplementation (50 or 100 uM). Developmental outcomes including survival, hatching, malformations, body length, and heart rate were assessed using microscopy and analyzed by ANOVA and Kaplan–Meier survival curves. High glucose significantly reduced survival (hazard ratio = 6.86; p < 0.0001), delayed hatching (median hatching time 84 vs. 60 hpf; HR = 0.17, 95% CI = 0.08–0.39; p < 0.0001), and induced growth retardation and bradycardia (p < 0.0001). L-carnitine did not rescue survival or hatching but partially ameliorated growth impairment (p < 0.05) and restored heart rate in a dose-dependent manner, with 100 uM supplementation approaching control values (p < 0.001). Morphological abnormalities such as yolk sac edema and spinal curvature remained present but less severe with co-treatment. In conclusion, L-carnitine confers partial protective effects on growth and cardiac function under hyperglycaemic stress, although it does not prevent early lethality.